An unusual case of hypercalcemia in a patient of concomitant hypoparathyroidism and celiac disease - Somani, Shrikant (Clin Cases Miner Bone Metab, 2016)
Milk alkali syndrome has shown resurgence with increase in use of (prescription or non prescription) calcium supplements. Cases of iatrogenic vitamin D intoxication has also increased due to increasing use of high doses of injectable vitamin D formulations by physicians, surgeons, orthopaedicians, gynecologists and other specialties inadvertently. Here, we present an unusual case of a 17-year-old boy who presented with iatrogenic hypercalcemia as a result of combination of milk alkali syndrome with vitamin D intoxication despite being a case of hypoparathyroidism and concomitantly suffering from celiac disease.